(untitled) (Indian Journal of Animal Production and Management, 2017)
To estimate the quantity and frequency of milk intake for optimum performance of Beetal kids during first 3 months of age, 36 newly born kids were randomly distributed into three groups i.e. T0, T1 and T2. The quantity of milk offered to each kid was 1/10th, 1/8th and 1/6th of their body weight during 1st month;1/12th, 1/10th& 1/8th during 2nd month and 1/14th, 1/12th& 1/10th during 3rd month in T0, T1 and T2 groups, respectively. Each group was further subdivided into 3 sub-groups (n=4 each) based on milk feeding frequency i.e. 2, 3 and 4 times per day as T02, T03, T04; T12, T13, T14 and T22, T23, T24, respectively. Creep feed and seasonal green fodder were offered from 15th days onwards to all the kids. Kids were observed for various parameters such as daily milk yield, feed intake, body weight gain, feed conversion ratio (FCR) and health status. Milk as well as concentrate feed intake was significantly (P<0.05) higher in thrice frequency groups (T03, T13 and T23). Green fodder intake showed almost similar pattern. Overall dry matter intake was also higher in thrice frequencygroups. Body weight of kids did not differ among the groups during different weeks of age. The overall average daily gain (ADG) was slightly lower in T0 groups than T1 and T2 groups. The FCR were almost similar in all the groups but it was marginally better in T0 group. It was concluded that enhancing the quantity of milk from 1/10th to 1/8th and 1/6th of body weight did not improve the performance of kids. Beetal kids of 0-3 months of age fed milk three or four times a day @1/10th, 1/12th and 1/14th of body weight during 1st, 2nd and 3rd month of age had marginally better performance than twice feeding a day.